Estimates for Diameter and Width for the Isoperimetrix in Minkowski Geometry
The following estimates are obtained for the diameterD_B(I) and the width Δ_B(I) of isoperimetrix in Minkowski space M^n4v_n-1 nv_nΔ_B(I)D_B(I)4v_n-1 v_n, where v_n is a volume of the unit ball in n-dimensional Euclidean space R^n. The first inequality turns into equality for a bicone, the last inequality turnsinto equality for a cube.Mathematics Subject Classification 2000: 52A38, 52A40., number=4, journal=Журнал математичної фізики, аналізу, геометрії, author=Diskant, V. I., year=2006, month=Груд, pages=388–395